Whistleblowing Dan Alasan Mahasiswa Melakukannya - Albertus Febri Christyawan; Aprina Nugrahesty Sulistya Hapsari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
College student life is inseparable from frauds, either academic fraud or in other forms. Students as the future leaders are required to prevent and stay away from all forms of fraud. One of the effective methods to prevent fraud is by disclosing fraud through whistleblowing. This study aims to analyze the effect of bystander effect phenomenon, religiosity, and retaliation on students' intention to do whistleblowing which focuses on student organizational life. This study uses primary data that obtained through a questionnaire that distributed and collected from 146 students who are the members of Faculty Economics and Business Universitas Kristen Satya Wacana Salatiga student organization as the research objects. The result proves that bystander effect and religiosity have negative and positive influence on the intention to do whistleblowing. Surprisingly, retaliation has a positive influence on students' intention to do whistleblowing. The result helps student organizations and other organizations to consider the factors that influence a person's intention to do whistleblowing, so the whistleblowing system can run effectively. Keywords: Whistleblowing intention, bystander effect, religiosity, retaliation